FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN CABAI RAWIT DI KOTA TOMOHON - Yosi ., Ratag; Paulus A. Pangemanan; Lorraine W. Th. Sondak (AGRI-SOSIOEKONOMI, 2018)
The study aims to analyze the factors that affected demand of cayenne pepper in Tomohon City. This study conducted for 3 months from September to November 2017. Data used secondary data was time series data per quarter from year 2012 to 2016. Analysis used is multiple regression analysis. The result showed that factor of, cayenne pepper price, substitution goods (curly pepper) and complementary goods (shallots) significantly affected on cayenne pepper demand.*lrr*.